Migratory stress of Bangladeshi international students in Canadian postsecondary institutions - Rahim, Rifatur (Journal of International Students, 2025)
Bangladeshi international students in Canada have strong academic and economic potential but lack proper social integration, which exacerbates their psychosocial challenges. This study aimed to explore their psychosocial challenges to unearth those issues. A qualitative study was conducted with 10 female and male students to examine their social, economic, and personal challenges and identify their coping strategies. This study found that international students go through migratory stress, which comprises various internal and external stressors such as second language anxiety, self-imposed isolation, homesickness, insufficient financial preparation, discrimination, safety concerns, lack of employment opportunities, and weather unsuitability. This study’s findings highlight the need for better social integration, employment opportunities, and mental health support for the students so they can better assimilate into Canadian society.